Validation of the NetSCID: an automated web-based adaptive version of the SCID - Benjamin B. Brodey; Michael First; Jared Linthicum; Kirsten Haman; Jordan W. Sasiela; David Ayer (Comprehensive Psychiatry, 2016)
The present study developed and validated a configurable, adaptive, web-based version of the Structured Clinical Interview for DSM, the NetSCID. The validation included 24 clinicians who administered the SCID and 230 participants who completed the paper SCID and/or the NetSCID. Data-entry errors, branching errors, and clinician satisfaction were quantified. Relative to the paper SCID, the NetSCID resulted in far fewer data-entry and branching errors. Clinicians ‘preferred’ using the NetSCID and found that the NetSCID was easier to administer.